2012
DOI: 10.3109/03630269.2012.721151
|View full text |Cite
|
Sign up to set email alerts
|

Study of Serum Hepcidin in Hereditary Hemolytic Anemias

Abstract: The aim of this study was to assess the level of hepcidin in hereditary chronic hemolytic anemias and to correlate the serum hepcidin levels to the need for blood transfusions (frequency of blood transfusions and the serum ferritin level). Seventy pediatric patients with hereditary chronic hemolytic anemias, attending to hematology clinics of Cairo University and Misr University for Science and Technology (MUST) hospitals were the subjects of this study [53 patients with β-thalassemia major (β-TM), 10 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
5
14
0
Order By: Relevance
“…For example, when a group of transfused β-thalassemia patients were compared to a group of SCD patients of similar age and equal mean total body iron loading (LIC), 20 to 30% of the thalassemia patients had cardiac dysfunction, gonadal failure, and growth delay whereas essentially none of the SCD patients had these problems [160]. This may be related to the lower levels of LPI [154] and relatively high hepcidin levels in SCD [161, 162]. …”
Section: Iron Toxicitymentioning
confidence: 99%
“…For example, when a group of transfused β-thalassemia patients were compared to a group of SCD patients of similar age and equal mean total body iron loading (LIC), 20 to 30% of the thalassemia patients had cardiac dysfunction, gonadal failure, and growth delay whereas essentially none of the SCD patients had these problems [160]. This may be related to the lower levels of LPI [154] and relatively high hepcidin levels in SCD [161, 162]. …”
Section: Iron Toxicitymentioning
confidence: 99%
“…30 Physiologically, cellular iron is exported by an iron export protein, ferroportin, which is negatively regulated by hepcidin. 31 In SCD patients, hepcidin levels can be either decreased 32 or increased. 33 We previously showed that expression of ferroportin inhibits HIV-1 replication and that hepcidin treatment increases intracellular iron and induces HIV-1 replication.…”
Section: Introductionmentioning
confidence: 99%
“…The peptide hormone hepcidin inhibits release of iron from macrophages, entrecotes, and hepatocytes into the plasma via degradation of a transmembrane iron exporter, ferroportin (Moayedi et al, ; Thephinlap et al, ). It is suggested that globin chain impairment in β‐thalassemia major causes ineffective erythropoiesis, anemia, and increased erythropoietin production, which results in enhanced erythroferrone production, an erythroid‐derived hormone that reduces hepcidin synthesis in the liver (El Beshlawy, Alaraby, Abdel Kader, Ahmed, & Abdelrahman, ).…”
Section: Discussionmentioning
confidence: 99%